2018
DOI: 10.1002/smtd.201800340
|View full text |Cite
|
Sign up to set email alerts
|

N2Reduction on Fe‐Based Complexes with Different Supporting Main‐Group Elements: Critical Roles of Anchor and Peripheral Ligands

Abstract: homogeneous and heterogeneous catalysts for N 2 reduction. [8][9][10][11][12][13][14][15] Artificial catalysts show a great potential because of high activity and tunability, as well as the flexibility to be incorporated into sophisticated electrode assemblies. [16][17][18] Various model catalyst complexes for N 2 reduction were synthesized, which contain low-oxidationstate central metal (such as Mo, Fe, Co, etc.) [19][20][21][22][23] and the supporting ligand that is invariably highly electron donating, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 70 publications
3
16
0
1
Order By: Relevance
“…128 There have been theoretical and experimental studies that demonstrated improved NRR performances by SACs in acidic or alkaline media. [21][22][23][24][25][26][27][28] Inspired by the Haber-Bosch process, Fe and Ru-based catalysts have been studied and synthesized for NRR electrocatalysis. Lü et al reported an isolated single Fe atomic sites supported on N-doped carbon frameworks (ISAS-Fe/NC) as a robust electrocatalyst for NRR in neutral media, with a FE of 18.6 ± 0.8% and a stable activity of more than 24 hours.…”
Section: Nitrogen Reduction Reaction (Nrr)mentioning
confidence: 99%
See 3 more Smart Citations
“…128 There have been theoretical and experimental studies that demonstrated improved NRR performances by SACs in acidic or alkaline media. [21][22][23][24][25][26][27][28] Inspired by the Haber-Bosch process, Fe and Ru-based catalysts have been studied and synthesized for NRR electrocatalysis. Lü et al reported an isolated single Fe atomic sites supported on N-doped carbon frameworks (ISAS-Fe/NC) as a robust electrocatalyst for NRR in neutral media, with a FE of 18.6 ± 0.8% and a stable activity of more than 24 hours.…”
Section: Nitrogen Reduction Reaction (Nrr)mentioning
confidence: 99%
“…SACs are considered as promising candidates for NRR electrocatalysis for its advantages of high atom utilization efficiency, unique electronic structures, and similarity of the coordination environments to the ligand fields of molecular NRR catalysts (Table 4). 128 There have been theoretical and experimental studies that demonstrated improved NRR performances by SACs in acidic or alkaline media 21‐28 . Inspired by the Haber‐Bosch process, Fe and Ru‐based catalysts have been studied and synthesized for NRR electrocatalysis.…”
Section: Electrochemical Application Of Single Atom Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…通过巧妙的分子设计,首次报道了 由 7 个碳原子组成的碳链(carbonlong)与金属形成的螯合物--芳香骨架基元-金属杂戊搭炔,随后 构筑了一系列原创性分子骨架基元--8-12 碳链螯合金属的全新芳香分子骨架,被誉为"碳龙同花 顺"的金属有机配合物(图 1) [7] ,开展了一类碳作为配位原子的金属芳香体系的原创性工作,逐步建 立新颖的具有中国特色的"碳龙化学" [8] [10] [10] 在首例铁基配合物高效仿生固氮的三角双锥构型(TPB)Fe 体系中 [12] ,金属 Fe 与缺电子特性的 B 原子形成了 Fe→B 配位 σ 键(图 3)。根据全活性空间自洽场(complete active space self-consistent field, CASSCF)的多参考计算,研究表明在[FeB]N − 2 中形成了不常见的 Fe (−1 价)氧化态,这种具有灵活氧 化还原特性的轴向配位键在单铁位点催化双氮还原的过程中发挥了重要作用 [13] 。根据配体所处能级 及电子占据情况,可将基于活性金属中心的配位键分为三种 [14] ,即配位键的成键电子全部来自配体 的 L-type、配位键的成键电子分别来自活性金属中心与配体的 X-type 以及配位键成键的电子全部来 自活性金属中心的 Z-type。 这套配位键类型的分类方式不以配位原子的金属性或非金属性进行区分, 而是从成键轨道上电子的归属进行划分,体现出基于活性金属中心的调节功能。通过分别构筑(TPX) Fe (锚原子 X = N, C, B)模型中轴向 Fe←N 键、Fe-C 键、Fe→B 键,对应的 L-type、X-type 和 Z-type 配位键在催化固氮过程中反映一定的作用规律(图 3) [15] 。对于单金属位点催化双氮合成氨的过程, 由于活性金属中心需要处于低价的富电子状态,形成 Z-type 类型的 M→Z 配位键可以构成"电子存 储"媒介 [16] [18] 。 在三或四卤代甲烷与 U 原子的反应产物中,他们发现了包含碳-铀三重键的锕系金属有机分子 HC≡UX 3 (X, Y = F, Cl, Br, I),首次揭示了 C≡U 三重键的存在及其稳定化的必要条件 [19] 。对其它 HCAnF 3 (An = Np, Pu, Am 和 Cm)配合物的研究发现,C-An 键随着原子序数的增加逐渐从三重键 变为单键。他们对具有最短 C-U 键长的 CUO 分子进行了全面的理论分析,发现在该端基 CUO 分 子中,存在着由未杂化的三个 C 2p 原子轨道和 C 2s 轨道部分参与的新型 CU 四重键,突破了碳原子最 高键级为三的传统观念 [20] 。在此基础上,他们把锕系 C-An 配合物扩展到了 Si-An 配合物。研究 发现了在 Si(μ-X)AnF 3 (An = Th, U; X = H, F)体系中,存在一种新颖的成键类型--多自由基成键(即 multiradical bonding) [21]…”
unclassified